2013
DOI: 10.4143/crt.2013.45.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cancer Screening Rates among Korean Men and Women: Results from the Korean National Cancer Screening Survey, 2004-2012

Abstract: PurposeThe Korean National Cancer Screening Survey (KNCSS), a nationwide, annual cross-sectional survey, has been conducted since 2004. The current study was conducted in order to report on trends in cancer screening rates for five types of cancer (stomach, liver, colorectal, breast, and cervix uteri).Materials and MethodsKNCSS data were collected between 2004 and 2012. The eligible study population included cancer-free men who were 40 years of age and older and women who were 30 years of age and older. The li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 16 publications
1
63
0
Order By: Relevance
“…The findings of this study revealed important information that only about 23% of the women who participated had undergone mammography regularly, which was lower than that of western countries, and even with other Asian countries (Kim et al, 2009;Huang et al, 2010). Indeed, over 30% of menopausal women in Hong Kong, Malaysia, Taiwan, and Thailand and over 60% of Korean women were adherent to regular mammography screening (Huang et al, 2010;Suh et al, 2013). Rates of mammography adherence in China, on the other hand, significantly differed between regions (Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…The findings of this study revealed important information that only about 23% of the women who participated had undergone mammography regularly, which was lower than that of western countries, and even with other Asian countries (Kim et al, 2009;Huang et al, 2010). Indeed, over 30% of menopausal women in Hong Kong, Malaysia, Taiwan, and Thailand and over 60% of Korean women were adherent to regular mammography screening (Huang et al, 2010;Suh et al, 2013). Rates of mammography adherence in China, on the other hand, significantly differed between regions (Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…According to the National Cancer Screening program of the republic of Korea, Korean adults over 40 years can receive endoscopic gastric cancer screening every other year. By 2012, gastric cancer screening rates reached 70% in the Republic of Korea [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the screening rate reported among Korean women residing in Korea is moderately low. In 2012, 77.1% of Korean women aged 30 years and older underwent a Pap test at least once in their lifetime, and 67.9% of the women had their most recent Pap test within the past 2 years (Suh, Choi, Lee, & Jun, 2013).…”
Section: Introductionmentioning
confidence: 99%